Digital finance and migrant workers' urban integration: The mediation effect of the gender-earning gap - Yang, Zhiheng; Liu, Tiantian; Xiao, Yao (Frontiers in Public Health, 2022)
In the context of wide application of digital finance, whether digital finance promotes or inhibits migrant workers’ urban integration is an important issue. Based on micro data of Chinese Social Survey (CSS) in 2019, we examined the impacts of digital inclusive finance on migrant workers' urban integration and explored its mechanisms. The empirical results show that digital finance promotes migrant workers to merge into urban life and has positive impacts, and the usage depth and digitization level of digital finance are positively correlated with assimilation process of urban migrant workers. Using the intermediary effect model, it is found that the development of digital finance promotes migrant workers merging into urban society by narrowing the gender gap in income. It significantly improves the ability of female migrant workers to obtain wealth and promotes their integration into cities and family migration. It is necessary to strengthen the promotion and utilization of digital finance to enhance their positive impact on the assimilation process of urban migrant workers by strengthening the construction of digital financial infrastructure, improving supporting policies related to development of digital finance, and improving financial literacy of migrant workers, especially female migrant workers.